Economy matters to fight against malnutrition: Results from a multicenter survey. Issue 1 (February 2017) - Klek, Stanislaw; Chourdakis, Michael; Bischoff, Stephan; Dubrov, Sergiej; Forbes, Alastair; Galas, Aleksander; Genton, Laurence; Gundogdu, Haldun R.; Irtun, Oivind; Jagmane, Ilze; Jakobson-Forbes, Triin; Jirka, Adam; et al.
Summary: Background and aim: Malnutrition represents a serious health care threat, as it increases morbidity, mortality and health care cost. The effective screening and treatment with enteral (EN) or parenteral (PN) nutrition are the key elements of the policy called Optimal Nutrition Care for All (ONCA). The study tried to analyze the impact of the state's economy on the implementation of EN and PN to define its role in ONCA. Material and methods: an international survey in twenty two European countries was performed between January and December 2014. An electronic questionnaire was distributed to 22 representatives of clinical nutrition (PEN) societies. The questionnaire comprised questions regarding country economy, reimbursement, education and the use EN and PN. Return rate was 90.1% (n = 20). Results: EN and PN were used in all countries surveyed (100%), but to different extent. The country's income significantly influenced the reimbursement for EN and PN (p < 0.05). It was also associated with the overall use of tube feeding and PN (p = 0.05), but not with the use of oral nutritional supplements (p = 0.165). The use of both, EN and PN at hospitals was not depended on the economy (p > 0.05). Education was actively carried out in all countries, however the teaching at the pre-graduate level was the least widespread, and also correlated with the country income (p = 0.042). Conclusions: Results indicated that economic situation influences all aspects of ONCA, including education and treatment. The reimbursement for EN and PN seemed to be the key factor of effective campaign against malnutrition.